The Thun-Hohenstein album : cultures of remembrance in a paper armory - Kirchhoff, Chassica (Boydell Press, 2023)
The first extensive study of the depiction of the armour in the Thun-Hohenstein Album, in the vibrant artistic and cultural contexts that created it.
Keywords: Armor -- History -- Pictorial works.; Armor -- Early works to 1800.; Armor in art.; Armures dans l'art.; HISTORY / Europe / Medieval; Armor; Armor in art; Early works; History; Pictorial works; Illustrated works.; Ouvrages illustrés.